Analysis of the hidden meaning of “Stopping by Woods on a Snowy Evening” poem through figurative languages - Wiranota, Hesti; Arifin, Muhammad Nur (Universitas Muhammadiyah Malang, 2024)
Stopping by Woods on a Snowy Evening is a popular poem written by Robert Frost in the 20th century, which reflected the social aspects of human existence. The researchers used the library research to analyze the figurative languages, the hidden meaning, and their correlation in poetry. The authors considered the hidden meanings in the poetry studied, namely that people should not be lulled by the promise or beauty of the surrounding environment; instead, they must complete their tasks before their lives end. The hidden meaning could be seen in the following stanzas: the stanza 1 depicted somebody stopping in a snowy forest, the stanza 2 revealed the small horse questioning a stop in a forest far from the farmhouse, the stanza 3 described the small horse shaking its harness bell as a warning, and the stanza 4 showed the speaker's determination to continue his journey and fulfill his duties before the end of his life. The correlation between the hidden meaning of